Distributed control of robotic networks : a mathematical approach to motion coordination algorithms - Bullo, Francesco; Cortés, Jorge, 1974-; Martínez, Sonia, 1974- (Princeton University Press, 2009)
This self-contained introduction to the distributed control of robotic networks offers a distinctive blend of computer science and control theory. The book presents a broad set of tools for understanding coordination algorithms, determining their correctness, and assessing their complexity; and it analyzes various cooperative strategies for tasks such as consensus, rendezvous, connectivity maintenance, deployment, and boundary estimation. The unifying theme is a formal model for robotic networks that explicitly incorporates their communication, sensing, control, and processing capabilities--a.
Keywords: Robotics.; Computer algorithms.; Robots -- Control systems.; Algorithms.; elektronické knihy; electronic books